What opportunities could the COVID-19 outbreak offer for sustainability transitions research on electricity and mobility? (2020)
The COVID-19 pandemic is a major landscape shock that is having pervasive effects across socio-technical systems. Due to its recentness, sustainability scientists and other researchers have only started to investigate the implications of this crisis. The COVID-19 outbreak presents a unique opportunity to analyze in real time the effects of a protracted landscape-scale perturbation on the trajectories of sustainability transitions. In this perspective, we explore the ramifications for sustainability transition research on electricity and mobility, drawing from selected examples in Finland and Sweden. The long-term consequences of the COVID-19 pandemic are likely to trigger more permanent changes connected to the digitalization of work and other daily activities, thus reducing mobility needs and overall fossil-energy consumption. The crisis may encourage governance systems to be better prepared for different types of shocks in the future, while it also contains a threat of increasingly populist or undemocratic political responses and increased securitization. These developments can guide research by addressing the reproduction of new practices arising from the COVID-19 outbreak to accelerate sustainability transitions, enhancing understanding of the role of governance in transitions, and bringing to attention the ethical and political implications of landscape shocks.